Does radical nephrectomy increase the risk of erectile dysfunction compared with partial nephrectomy? A cohort analysis. (3rd July 2012) - Kopp, Ryan P.; Dicks, Brian M.; Goldstein, Irwin; Mehrazin, Reza; Silberstein, Jonathan L.; Colangelo, Caroline J.; Bagrodia, Aditya; Bazzi, Wassim M.; Wake, Robert W.; Patterson, Anthony L.; Kane, Christopher J.; Wan, Jim Y.; et al.
Abstract : Study Type – Therapy (prospective cohort) Level of Evidence 2b What's known on the subject? and What does the study add? Erectile dysfunction (ED) is a form of endothelial dysfunction that is prevalent in patients with chronic kidney disease (CKD). We hypothesized that partial nephrectomy (PN) would limit development of ED compared with radical nephrectomy (RN), primarily due to renal function preservation, and found that patients undergoing RN had significantly higher de novo ED compared with a contemporary, well‐matched cohort undergoing PN; in addition to RN, hypertension, CKD and diabetes mellitus were associated with developing ED. To our knowledge, this is the first study demonstrating an increased risk of ED after RN compared with PN. OBJECTIVES: To evaluate prevalence and risk factors for development of erectile dysfunction (ED) in patients who underwent radical nephrectomy (RN) and partial nephrectomy (PN). ED is a form of endothelial dysfunction that is prevalent in patients with chronic kidney disease (CKD). PN confers superior renal functional preservation compared with RN; however, the impact on ED is unclear. METHODS: This was a retrospective study of 432 patients (264 RN/168 PN, mean age 58 years, mean follow‐up 5.8 years) who underwent surgery for renal tumours between January 1998 and December 2007. The primary outcome was rate of de novo ED postoperatively. Secondary outcomes included development of CKD (estimated GFR < 60 mL/min/1.73 m 2 ) and response to phosphodiesterase‐5 inhibitors. Multivariate analysis was performed to determine risk factors for de novo ED postoperatively. RESULTS: RN and PN groups had similar demographics and comorbidities. Tumour size (cm) was larger for RN (RN 7.0 vs PN 3.7, P < 0.001) and more preoperative ED existed in PN vs RN ( P = 0.042). No differences were observed for preoperative CKD, hyperlipidaemia and diabetes mellitus. Postoperatively, higher rates of de novo ED (29.5% vs 9.5%, P < 0.001) and CKD (33.0% vs 9.8%, P < 0.001) developed in RN vs PN cohorts, respectively. Of men with ED, 63% responded to phosphodiesterase inhibitors, without significant difference between the two groups ( P = 0.896). Multivariate analysis demonstrated de novo ED to be associated with RN (odds ratio [OR] 3.56, P < 0.001), hypertension (OR 2.32, P = 0.014), preoperative (OR 8.77, P < 0.001) and postoperative (OR 2.64, P = 0.001) CKD, and postoperative diabetes mellitus (OR 2.93, P < 0.001). CONCLUSIONS: Patients undergoing RN had significantly higher de novo ED compared with a contemporary, well‐matched cohort undergoing PN. In addition to RN, hypertension, CKD and diabetes mellitus were associated with developing ED. Further investigation on effects of surgically induced nephron loss on ED is requisite.